Functional Activation of G-Proteins Coupled With Muscarinic Acetylcholine Receptors in Rat Brain Membranes - Yuji Odagaki; Masakazu Kinoshita; Ryoichi Toyoshima (Elsevier, 2014)
Abstract.: The functional activation of Gi/o proteins coupled to muscarinic acetylcholine receptors (mAChRs) was investigated with the conventional guanosine-5'-O-(3-[35S]thio)triphosphate ([35S]GTPγS) binding assay in rat brain membranes. The most efficacious stimulation elicited by acetylcholine or carbachol (CCh) was obtained in striatal membranes. The pharmacological properties of mAChR-mediated [35S]GTPγS binding determined with a series of muscarinic agonists and antagonists were almost identical among the three brain regions investigated, i.e., cerebral cortex, hippocampus, and striatum, except for the apparent partial agonist effects of (αR)-α-cyclopentyl-α-hydroxy-N-[1-(4-methyl-3-pentenyl)-4-piperidinyl]benzeneacetamide fumarate (J 104129) observed only in the hippocampus, but not in the other two regions. Among the muscarinic toxins investigated, only MT3 attenuated CCh-stimulated [35S]GTPγS binding. The highly selective allosteric potentiator at the M4 mAChR subtype, 3-amino-N-[(4-chlorophenyl) methyl]-4,6-dimethylthieno[2,3-b]pyridine-2-carboxamide (VU 10010), shifted the concentration-response curve for CCh leftwards as well as upwards. On the other hand, neither thiochrome nor brucine N-oxide was effective. The increases induced by CCh and 5-HT were essentially additive, though not completely, indicating that the mAChRs and 5-HT1A receptors were coupled independently to distinct pools of Gi/o proteins. Collectively, all of the data suggest that functional activation of Gi/o proteins coupled to mAChRs, especially the M4 subtype, is detectable by means of CCh-stimulated [35S]GTPγS binding assay in rat discrete brain regions. Keywords:: muscarinic acetylcholine receptor, G-protein, [35S]GTPγS binding, muscarinic toxin, allosteric modulator